2006
DOI: 10.1111/j.1755-0238.2006.tb00060.x
|View full text |Cite
|
Sign up to set email alerts
|

An evaluation of biological and abiotic controls for grapevine powdery mildew. 2. Vineyard trials

Abstract: Grapevine powdery mildew (Erysiphe necator) affects grape yield and fruit quality worldwide. Managers of conventional vineyards rely mainly on synthetic fungicides and sulfur to control powdery mildew, while in organic vineyards sulfur is the main control agent, often in rotation with canola‐based oils, bicarbonates and biological control agents. The efficacy of those materials has not been evaluated critically under field conditions in Australia. Accordingly, a range of materials showing most promise in previ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
14
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 23 publications
(15 citation statements)
references
References 14 publications
1
14
0
Order By: Relevance
“…Furthermore, the variable spray distribution and the large canopy type may have contributed to the poor control of disease. Crisp et al (2006b) reported similar results in South Australia where similar test materials failed to control powdery mildew adequately due to a large, dense canopy. As these 'alternative' materials probably act as contact fungicides, it is important that spray coverage is maximised (Crisp et al 2006c) and that vine vigour is controlled.…”
Section: Discussionsupporting
confidence: 80%
See 2 more Smart Citations
“…Furthermore, the variable spray distribution and the large canopy type may have contributed to the poor control of disease. Crisp et al (2006b) reported similar results in South Australia where similar test materials failed to control powdery mildew adequately due to a large, dense canopy. As these 'alternative' materials probably act as contact fungicides, it is important that spray coverage is maximised (Crisp et al 2006c) and that vine vigour is controlled.…”
Section: Discussionsupporting
confidence: 80%
“…Results of trials during three grape growing seasons suggest that 'alternatives' to sulfur would be suited to controlling powdery mildew on less susceptible cultivars such as Cabernet Sauvignon (Doster and Schnathorst 1985) and Shiraz rather than Chardonnay (Crisp et al 2006b). Control of powdery mildew early in the season using an effective fungicide is crucial in warm, dry regions, after which time 'alternative' materials such as milk and whey may be used.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…The international bibliography concerning the production of organic grapes covers different aspects of this field, such as those related to a) minimize the use and effect of copper application (Dagostin et al, 2011); b) search alternative products for different diseases (Crisp et al, 2006); c) control nematodes (Coll et al, 2012); d) fertilization and mineral nutrition (Coll et al, 2011); e) the impact and evaluation of the organic viticulture (Reeve et al, 2005;Fragoulis et al, 2009). Serra Gaúcha, the most important Brazilian viticultural region was also influenced by this scientific and technological development with the use of different agricultural inputs − such as fungicides, insecticides, herbicides, growth regulators, fertilizers −, and enological -such as yeasts, enzymes, stabilizers, antioxidants.…”
Section: Introductionmentioning
confidence: 99%
“…For example, potassium bicarbonate represents a practicable alternative to synthetic chemical fungicides or sulphur (Crisp et al, 2006), although it is commonly less effective than these ones. Other examples are plant extracts and seaweed (laminarin), COS-OGA, chitin or chitosan mainly act by inducing systemic resistance in the plant (Iriti et al, 2011;van Aubel et al, 2014;Vera et al, 2011).…”
Section: Leaf and Bunch Diseasementioning
confidence: 99%